2020
DOI: 10.4084/mjhid.2020.014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chemotherapy and hematopoietic stem cell transplantation on humoral immunity to vaccine-preventable diseases

Abstract: BACKGROUND, OBJECTIVES The antibody titer of vaccine-preventable disease in 70 patients who underwent chemotherapy or haemopoietic stem cell transplantation (HSCT) was assessed in order to evaluate the seroprotection after treatment and the feasibility and the efficacy of a policy of revaccination. METHODS Serum antibody titers of 70 patients for hepatitis B (HBV), Rubella, Varicella-zoster (VZV), Measles, Mumps, Polio viruses, Clostridium tetani (C. tetani) and Streptococcus pneumoniae (S. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(44 citation statements)
references
References 22 publications
0
26
0
18
Order By: Relevance
“…Previous findings suggested that chemotherapy can have profound and long-lasting negative effects on the bone marrow immune system for up to nine months after treatment and so leaving patients vulnerable to opportunity and secondary infections ( 37 ). So, a single booster dose of Covid-19 vaccine might be a beneficial approach to promote vaccine immunity performance after chemotherapy ( 38 ). Immunity response after co-administration of trastuzumab and chemotherapy has synergic effects meaning that in normal circumstances trastuzumab can improve humoral immune response but our study has a revers relationship with it ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggested that chemotherapy can have profound and long-lasting negative effects on the bone marrow immune system for up to nine months after treatment and so leaving patients vulnerable to opportunity and secondary infections ( 37 ). So, a single booster dose of Covid-19 vaccine might be a beneficial approach to promote vaccine immunity performance after chemotherapy ( 38 ). Immunity response after co-administration of trastuzumab and chemotherapy has synergic effects meaning that in normal circumstances trastuzumab can improve humoral immune response but our study has a revers relationship with it ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports found that the younger age was significantly different in terms of losing protective antibody levels, 2 possibly related to ineffective vaccination or an incomplete national vaccination program at younger ages 14 . Toret et al 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Toret et al 2 reported 46 fully vaccinated pediatric ALL survivors among whom 93% had nonprotective antibody levels for at least one vaccine-preventable disease. Fayea et al 13 observed that more than 90% of their patients were seronegative for at least one vaccine-preventable disease, and Garonzi et al 14 reported that 83% of their patients had nonprotective antibody levels for at least one vaccine-preventable disease. Cesaro et al's 15 literature searchfrom 1980 to 2013 revealed that the incidence of a lack of protective antibody titersas measured 6-12 months after chemotherapy varied according the type ofvaccine: it was higher for HBV (about 50% of patients) and lower for measles,mumps, rubella (20%-40%), and polio-diphtheria-tetanus (10%-30%) (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, Kotecha et al 21 declararon que en 100 pacientes, el 80% era susceptible a la cepa H3N2, el 67% a la H1N1 y el 88% a la cepa B. -Poliovirus: Garonzi et al 12 reportaron que en 34 pacientes que después de la quimioterapia no tenían protección contra la enfermedad, los títulos de protección para cada tipo de poliovirus era del 26% para el tipo 1, el 24% para el tipo 2 y el 21% para el tipo 3. -Clostridium tetani: Garonzi et al 12…”
Section: ¿Cuál Es El Efecto Del Tratamiento Contra El Cáncer Sobre Lo...unclassified
“…-Sarampión, paperas y rubéola: Bettoni et al 11 , respecto al sarampión, paperas y rubéola, recomiendan posponer cualquier vacuna viva hasta después del primer año de tratamiento con inhibidores de la tirosina cinasa. En la misma línea, Garonzi et al 12 declaran que la aplicación de inmunobiológicos después de la quimioterapia debe realizarse de 6 a 12 meses posteriores. Otros dos estudios 15,22 recomiendan la revacunación como un medio de bajo costo para la prevención de enfermedades prevenibles, pero no indican el periodo de tiempo para la administración.…”
Section: ¿Se Recomienda Administrar Dosis De Refuerzo De Vacunas En E...unclassified